Women's Leadership in Da'wah Management: As-Salmaniyah Islamic Boarding School, Mandailing Natal - Rini Shofiah Pohan; Elismayanti Rambe; Rahmi Wahyuni (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2025)
This research examines women's leadership roles in enhancing dakwah program management at As-Salmaniyah Al-Yusufiah Tahfidz Islamic Boarding School, Mandailing Natal Regency, North Sumatra—the sole female-led pesantren among 270 institutions in the region. Despite persistent patriarchal cultural norms, women's leadership demonstrates substantial effectiveness in Islamic educational contexts through transformational approaches integrating participatory decision-making (musyawarah), exemplary behavior (uswah hasanah), and spiritual development (tazkiyatun nafs). This qualitative case study employed in-depth interviews with pesantren leadership, teachers, students, and community members, direct observations of dakwah program implementation, and document analysis of institutional records from March to June 2025. Findings reveal measurable impacts: student enrollment increased from 220 (2018) to 318 (2024), representing 44.5% growth; complete Qur'an memorization achievement rose from 8 students (3.6%) to 35 students (11%); Musabaqah Tilawatil Qur'an competition winners increased from 5 to 25 students; and 40% of alumni gained acceptance to State Islamic Universities. External collaboration generated IDR 500 million in waqf funding (300% increase) and expanded dakwah programs to 10 surrounding villages. While facing challenges including patriarchal resistance, limited resources, and dual domestic-professional roles, female leadership successfully employs adaptive strategies emphasizing Islamic role models, external partnerships, spiritual guidance, and economic empowerment. This research contributes theoretically by validating transformational leadership theory within Islamic boarding school contexts and practically by providing replicable best practice models for gender-inclusive pesantren management.